Organizing the Exploitation of Vulnerable People : A Qualitative Assessment of Human Trafficking - Shepherd, Dean A.; Parida, Vinit; Williams, Trent; Wincent, Joakim (SAGE Publishing, 2021)
Focusing on the organizing practices by which vulnerable individuals are exploited for their labor, we build a model that depicts how human traffickers systematically target impoverished girls and women and transform their autonomous objection into unquestioned compliance. Drawing from qualitative interviews with women forced into labor in the sex industry, human traffickers, brothel managers, and other sources (e.g., doctors, nongovernment organizations, and police officers fighting human trafficking), we inductively theorize that organizing of vulnerable individuals for human exploitation involves four interrelated practices—(1) deceptive recruiting of the vulnerable, (2) entrapping through isolation, (3) extinguishing alternatives by building barriers, and (4) converting the exploited into exploiters—that together erode and eventually eliminate workers’ autonomy. We conclude by discussing implications of our research for theory—specifically, the literature on human exploitation and loss of worker agency.
Keywords: deviant/counterproductive behavior; power and politics; grounded theory; conflict management; fi=Strateginen johtaminen|en=Strategic Management|